ALTERNATIF PENGGUNAAN PLASTIK POLYPROPYLENE PADA CAMPURAN ASPAL - Samsul Arif (Civilla : Jurnal Teknik Sipil Universitas Islam Lamongan, 2018)
Asphalt is a thermoplastic material that will become harder or thicker if the temperature is reduced and will be soft or more liquid if the temperature increases. As developments in asphalt mixtures, several studies have developed the use of plastic waste in an effort to reduce plastic waste that is difficult to recycle. In this research used type of PP plastic (Polypropylene) as alternative of asphalt mixture. the results of the study showed the lowest stability value that is on the normal laston of 1136 kg, but the value still meets the specification of Bina Marga> 800kg. The lowest flow is on the normal laston of 3.62, the value still meets the provisions of Bina Marga > 3. The lowest Marshall Quotient value on the normal 307, is still meets the requirements of Bina Marga > 250. With the addition of PP plastic (Polypropylene) 2% and 4% showed better results than normal asphalt. Judging from the stability, flow and MQ values, they are better than the normal asphalt.